Bilateral pulmonary thromboendarterectomy for chronic thromboembolic pulmonary hypertension: The youngest case in our region [Kronik tromboembolik pulmoner hipertansiyon nedeniyle uygulanan iki tarafli pulmoner tromboendarterektomi: Bólgemizdeki en kücük olgu] - (:unkn) unknown (Turkish Anaesthesiology and Intensive Care Society, 2013)
The insertion of ventriculoatrial (VA) shunts for the treatment of hydrocephalus is associated with the development of chronic thromboembolic pulmonary hypertension (CTEPH). Chronic thromboembolic pulmonary hypertension occurs in patients with recurrent or chronic pulmonary embolism, and is a rare but, potentially devastating disease in children. Pulmonary thromboendarterectomy (PTE) is an important curative therapy for patients with CTEPH. Herein, we present a case of a 14 year-old male patient with CTEPH that developed after a VA shunt procedure. After successful PTE, systolic pulmonary artery pressure was decreased from 75 mmHg to 30 mmHg. PTE is recommended in the pediatric CTEPH population. © 2013 Türk Kardiyoloji Derneǧi.
Keywords: Antihypertensive agents/therapeutic use; Child; Chronic disease; Endarterectomy/methods; Hypertension, pulmonary/etiology; Thromboembolism/complications